2017
DOI: 10.1177/2325967117726976
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Aerobic Fitness Predicts In-Season Injury and Illness in Female Youth Athletes

Abstract: Background:Although preseason aerobic fitness has been suggested as a modifiable risk factor for injury in adult athletes, the relationship between aerobic fitness, injury, and illness in youth athletes is unknown.Purpose:To determine whether preseason aerobic fitness predicts in-season injury and illness risk in female adolescent soccer players.Study Design:Case-control study; Level of evidence, 3.Methods:Fifty-four female adolescent soccer players underwent preseason evaluation to determine years of experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…Online resource 3 outlines the key data extracted for this review. Of the 44 studies included, the most frequently studied team ball sport was soccer (represented in 24 studies; 55%) [ 61 84 ], followed by basketball (represented in 14 studies, 32%) [ 64 , 65 , 71 , 73 , 83 , 85 – 93 ], and volleyball (represented in 7 studies, 16%) [ 64 , 71 , 83 , 89 91 , 94 ]. Other team ball sports investigated included handball [ 81 , 90 , 95 , 96 ], netball [ 97 100 ], softball [ 101 103 ], field hockey [ 61 , 65 ], lacrosse [ 61 ], and rugby union [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online resource 3 outlines the key data extracted for this review. Of the 44 studies included, the most frequently studied team ball sport was soccer (represented in 24 studies; 55%) [ 61 84 ], followed by basketball (represented in 14 studies, 32%) [ 64 , 65 , 71 , 73 , 83 , 85 – 93 ], and volleyball (represented in 7 studies, 16%) [ 64 , 71 , 83 , 89 91 , 94 ]. Other team ball sports investigated included handball [ 81 , 90 , 95 , 96 ], netball [ 97 100 ], softball [ 101 103 ], field hockey [ 61 , 65 ], lacrosse [ 61 ], and rugby union [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study did not report an injury definition to classify ‘any injury’ [ 70 ]. One prospective study (level II) investigated ‘any injury’ regarding total days injured [ 104 ], whereas the remaining studies examined any physical injury that occurred during sport using either prospective (level II) [ 64 , 66 68 ], case-control (level III) [ 84 ], or cross-sectional study designs (level III) [ 70 , 76 , 102 ]. Two cross-sectional studies (level III) examined participants’ one-season [ 102 ] or three-season [ 76 ] history of ‘any injury’.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies related to various elements of physical fitness have attempted to identify factors that contribute to injury and illness risk in young athletes, although not at the elite level. Typically, physical fitness tests encompass components such as cardiorespiratory endurance, muscular strength, flexibility tests, and functional movement tests . Prior research studies on the adult population have demonstrated an association between higher levels of aerobic fitness and decreased injury risk, whereas research on the relationship between physical fitness level and illness risk is limited and mostly focus on increasing training loads .…”
Section: Introductionmentioning
confidence: 99%
“…For youth elite athletes, there are even less data addressing the relationship between physical fitness and injury and illness risk and the results are conflicting . While some studies claim that well‐developed aerobic fitness might protect youth athletes from future injury or illness, no association has been shown with functional movement screening tests, nor with a relatively lower fitness level …”
Section: Introductionmentioning
confidence: 99%
“…Intervensi di luar musim kompetisi untuk mempromosikan kebugaran aerobik dapat membantu mengurangi risiko kehilangan waktu selama musim kompetisi karena cedera. 31…”
Section: Kebugaranunclassified